Female labour supply and informal employment in Ecuador - H. Xavier Jara; Pia Rattenhuber (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2022)
Low- and middle-income countries face a trade-off between raising tax revenue to strengthen social protection and creating incentives for the population to enter formal employment. However, empirical evidence on labour supply elasticities in the presence of informal employment remains scarce. This paper analyses female labour supply behaviour and the choice between formal and informal employment in Ecuador, a middle-income country characterized by persistent levels of informal employment particularly among women. We use two methods to estimate and compare formal employment elasticities: (i) a discrete choice model of labour supply with informality and (ii) grouped-data estimation techniques. For identification, we exploit variation in tax-benefit policies covering the period 2011-19, using microsimulation techniques applied to household survey data. Our results show that, on average, formal employment elasticities for single women are low regardless of the approach chosen. However, for women in couples, formal employment elasticities are larger under the discrete choice approach whereas they are low and non-significant under the grouped-data estimations.
Keywords: J23; J42; 330; labour supply; informal employment; tax-benefit policies; Ecuador